Translation and psychometric evaluation of the Chinese version of the Heart Failure-Specific Health Literacy Scale - Meng Yue; Lijun Zhang; Yuanyuan Lu; Changde Jin (Elsevier, 2016)
Objective: Health literacy is closely associated with self-care behaviors in heart-failure patient. A reliable, valid, and practical measuring tool would evaluated the level of health literacy in Chinese patients with heart failure, and provide evidence for individualized education. Aim of this study was to translate Heart Failure-Specific Health Literacy Scale (HF-Specific HL Scale) into Chinese and test the reliability and validity of the Chinese version. Methods: The original HF-specific HL scale was translated into Chinese and modified for cultural adaption. Totally 164 HF inpatients were investigated with the Chinese version of HF-specific HL scale. To test the reliability and validity of the scale, item analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and correlation analysis were conducted. Result: Cronbach's α value for the scale is 0.87; the correlation coefficients between each item and the total score ranged from 0.61 to 0.91. Three factors was extracted by EFA, which could explain 64.62% of the total variance. The result of CFA also showed that the scale demonstrated an acceptable model fit. The scale was significantly correlated with the Chinese version of the Heart Failure Knowledge Test (C-HFKT). Conclusion: The Chinese version of HF-specific HL scale is reliable and valid, and is suitable for assessment of HL in Chinese HF patients.